Os movimentos discursivos da instância-sujeito Marina Silva - Rocha, Bruna Brenda Siqueira (2017)
In this present paper, I intend to analyze the statements of the subject-instance Marina Silva enounced in the scope of Brazilian policy. For this purpose, I am based on the French Discourse Analysis which, due to its epistemological conjuncture that is based on Linguistics, Lacanian Psychoanalysis and Marxism (historical materialism) principles. It will work as a support for the development of this research. In addition, I will take as theoretical basis assumptions by Michel Pêcheux, once, through this framework, I will be able to interpret the effects of meaning that emerge from the statements enounced by a subject-instance that moves in its discursive inscriptions in the emergence of occupied discursive places. I have as general objective to analyze movements in the political discursive inscriptions of the subject-instance Marina Silva and, as a specific objective, to identify different subject-positions, that is, places in which it is inscribed, explaining and interpreting the displacements, transformations and ideological movements. I start from the hypothesis that, in the political statements of this subject-instance, there are discursive movements that will lead to ideological displacements, movements and transformations established in the different subjectinstance in which, possibly, it inscribes itself to put itself in the field of the Brazilian politics. Moreover, I believe that these processes are concerned to the different political moments in which it was inserted and in which it was subscribed, wheter in PT, PV, PSB or REDE. I hope this research can contribute to make society get itself in a critical position, concerning to statements which circulate in the field of Brazilian policy and ideology imbricated to it. Therefore, this paper is justified by the interest in deepening studies on the functioning of a subject-instance that, in this investigation, moves within its discursive inscriptions, assuming different subject-positions in processes of identification, counteridentification and disidentification. In advance, from the corpus, emerged different subject-positions activist/environmentalist; petista; candidate for the presidency of the Republic and; anti-PT. From these occupied places, I was able to identify movements in the discursive of displacement, movement and ideological transformation; which confirmed the hypothesis raised. Key-words: Discourse Analysis, subject-instance, Marina Silva, discursive movements